Revolutionary Universalism in 19th-century Haitian Poetry. An Ideological Reappropriation (ACME, 2024)
As part of the recent attempts to rediscover and rehabilitate the historical and literary context of 19th-century Haiti, this article aims to explore the expression of revolutionary universalism in Haitian poets of the 19th century, offering a new perspective on their use of classical imagery. It seeks to reconsider the traditional perception of these poets to reveal the often-ignored ideological depth of their writings, rooted in the republican values of the Enlightenment. In response to the racist accusations from the Metropole – which reduce the insurrection that led to the country’s declaration of Independence in 1804 to a matter of race – the Haitian poets adopted an epic and nationalist imagery that claimed an explicit connection with the universalism of the French Revolution. This imagery is not a mere stylistic borrowing, but a committed adherence to the universal ideals of the République, as well as a proof of the active role of Haitian intellectuals in the international debate on the abolition of slavery. After a description of the historical and political contextualization in which Haiti’s national poetry was born and developed, this study will focus on the analysis of the revolutionary iconography in the early Haitian poetic production.
Keywords: Revolutionary universalism; Haitian poets; 19th-century Haiti; revolutionary iconography; classical imagery